P 74 Subthalamic beta dynamics mirror parkinsonian bradykinesia months after neurostimulator implantation. Issue 10 (October 2017) - Steiner, L.A.; Neumann, W.J.; Straub, F.; Pogosyan, A.; Herz, D.; Tan, H.; Kuhn, A.A.; Brown, P.
Abstract : Background: Exaggerated oscillatory activity in the beta frequency band in the subthalamic nucleus has been suggested to be related to bradykinesia in Parkinson's disease (PD). However, past studies have been limited to recordings obtained in the postoperative, stun-effect affected period, and have seldom reported evidence of this effect within, as opposed to across, patients. Methods: Here we investigate how beta power dynamics in the local field potential relate to changes in kinematic parameters in an upper limb alternating pronation and supination task in PD patients several months after neurostimulator implantation. Local field potentials were recorded from a fully implanted pulse generator (Activa PC+S, Medtronic, Inc.) and motor performance simultaneously tracked. Results: While beta power was suppressed during repeated movements, this suppression progressively fell off in tandem with a decrement in the frequency and speed of movements over time. This was significant both within and across patients. Discussion: These findings provide further evidence that beta power may serve as a biomarker for bradykinesia and thus be a suitable feedback input for chronic adaptive deep brain stimulation.